Gateways 1 : - Kimbrough, Victoria (Oxford Univ. Press, 1998)
The book features core vocabulary, acarefully structured grammar syllabus, cross-cultural topics, key learning strategiesintegrated into each unit and consolidated in the Strategy Session review units